Lack of progressive reduction in P3 amplitude after the first–episode of schizophrenia: A 6-year follow-up study - Devrim-Üçok, Müge; Keskin-Ergen, Yasemin; Üçok, Alp (Psychiatry research, 2016)
P3 event-related potential may track the course of neurophysiological pathology in schizophrenia. Reduction in the amplitude of the auditory P3 is a widely replicated finding, already present at the first psychotic episode, in schizophrenia. Whether a progressive deficit is present in auditory P3 in schizophrenia over the course of illness is yet to be clarified. Previous longitudinal studies did not report any change in P3 over time in schizophrenia. However, these studies have been inconclusive, because of their relatively short follow-up periods, lack of follow-up data on controls, and assessment of patients already at the chronic stages of schizophrenia. Auditory P3 potentials, elicited by an oddball paradigm, were assessed in 14 patients with first-episode schizophrenia and 22 healthy controls at baseline and at the 6-year follow-up. P3 amplitudes were smaller in patients with first-episode schizophrenia than in controls. Importantly, over the 6-year interval, the P3 amplitudes were reduced in controls, but they did not change in patients. The lack of P3 reduction over time in patients with schizophrenia might be explained by the maximal reduction in P3 already at baseline or by the alleviation of P3 reduction over time. •The longitudinal course of auditory P3 was evaluated in patients with first-episode schizophrenia.•The study had a long follow-up period (6 years), and follow-up data on controls were collected.•P3 amplitudes were smaller in patients than in controls.•A lack of progressive reduction in P3 was noted in patients over time compared to controls.